2020
DOI: 10.1002/ls.1506
|View full text |Cite
|
Sign up to set email alerts
|

Effect of few layer graphene additive on the tribological properties of lithium grease

Abstract: The tribological properties of lithium grease with few layer graphene (FLG) additive were studied. Three-dimensional surface topography, FESEM with EDS and XPS were used to analyse the morphology, distribution of elements and chemical states on the wear spots. The results show that 0.1 wt% FLG content produced maximum reduction rate of the friction coefficient and minimum wear spot diameter (WSD). And the best results obtained under larger load and lower speed. Fe 3 O 4 was found to be the main component of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…By contrast, grease is more applicable in certain cases owing to its semisolid characteristic, which helps to protect equipment from pollutants and reduce noise. Due to its excellent tolerance of water and anti-rust property, lithium grease is one of the most commonly used greases in the industry [7][8][9]. Lithium grease is composed of colloidal suspensions formed by dispersing thickeners and additives in mineral or synthetic oils.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, grease is more applicable in certain cases owing to its semisolid characteristic, which helps to protect equipment from pollutants and reduce noise. Due to its excellent tolerance of water and anti-rust property, lithium grease is one of the most commonly used greases in the industry [7][8][9]. Lithium grease is composed of colloidal suspensions formed by dispersing thickeners and additives in mineral or synthetic oils.…”
Section: Introductionmentioning
confidence: 99%
“…As for the attapulgite grease with graphene, it possess better tribological properties than the base grease, which can be ascribed to the following two aspects: (1) graphene nanosheets could generate physical deposition tribofilm on the worn surface to reduce friction and wear 16–18 . (2) graphene may be served as catalyser to promote the tribochemical reactions.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, graphene has got great attention in the field of tribology benefiting from its high chemical stability, high load‐bearing capacity and good interlaminar slip property. In particular, there are a lot of reports concerning the study of graphene as lubricating additives for several kinds of greases recently 16–21 . The results indicated that graphene can improve the friction‐reducing and antiwear properties of the greases.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover corresponding to the grease-B case, the peaks of Fe 3 p3/2 and O1s-C were found at 709.7 and 531.2 eV, respectively. These further indicate the formation of Fe 3 O 4 [37][38][39][40]. The main component found corresponding to grease-A is Fe 2 O 3 ; however, Fe 2 O 3 and The wear scars on the balls and tracks on plates of conventional and textured concentrated contacts have been presented in figures 12 and 13, respectively.…”
Section: Wearmentioning
confidence: 93%